Pengelolaan Wakaf Uang pada KSPPS BMT NU Ngasem Bojonegoro Perspektif terkait PERMEN Nomor 16/Per/M.KUKM/IX/2015 - Yani (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2023)
Regulation of implementation of collection and management of money waqf on the Sharia Cooperatives/BMT is PERMEN number 16/Per/M-KUKM/IX/2015. Money Waqf is expected to be a source of funding to strengthen the cooperative capital and become cheap funds without any cost to be then disbursed for the community to be more productive. This study aims to analyze the implementation of the management of money waqf implemented aspect by KSPPS BMT NU of Ngasem Bojonegoro after the issuance of PERMEN No. 16/Per/M-KUKM/IX/2015. This study uses the descriptive method, by collecting the data in the field using observation, interview, and documentation techniques. The results of collection and management of money waqf in KSPPS BMT NU Ngasem Bojonegoro in 2016-2017 amounted to Rp 438.242.000,00. With a total waqf of 34,302 people. The money waqf management is invested in the form of time deposits in Baitul Tanwil Division with an investment of Rp 38.242.000,00 with profit sharing of Rp 27.513.960,00. It is advised to KSPPS BMT NU Ngasem Bojonegoro to improve the quality and quantity of SDM kenazhiran through a waqf education program to develop the understanding of waqf management, utilization, and investment money waqf in the productive sector.